PERSONALITY-ORIENTED APPROXIMATION MODELS EDUCATIONAL ACTIVITIES FUTURE AVIATION EXPERTS PROFILE - Ладогубець, Н. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
In the article the theoretical and methodological foundations for the creation of approximating personality-oriented mathematical model of training aviation professionals profile based on personal preferences of the individual. This model is provides maximum disclosure of individual abilities of the individual, taking into account the unique features of the psyche of the educational process and training of future specialists with the context - competence approach